Rational design of an influenza-COVID-19 chimeric protective vaccine with HA-stalk and S-RBD - Yulei Li; Peipei Liu; Tianjiao Hao; Sheng Liu; Xi Wang; Yufeng Xie; Ke Xu; Wenwen Lei; Cheng Zhang; Pu Han; Ying Li; Xiyue Jin; et al. (Emerging Microbes and Infections)
Highly contagious respiratory illnesses like influenza and COVID-19 pose serious risks to public health. A two-in-one vaccine would be ideal to avoid multiple vaccinations for these diseases. Here, we generated a chimeric receptor binding domain of the spike protein (S-RBD) and hemagglutinin (HA)-stalk-based vaccine for both SARS-CoV-2 and influenza viruses. The S-RBD from SARS-CoV-2 Delta was fused to the headless HA from H1N1 (H1Delta), creating a chimera that forms trimers in solution. The cryo-electron microscopy structure of the chimeric protein complexed with the RBD-targeting CB6 and the HA-stalk-targeting CR9114 antibodies shows that the trimeric protein is stable and accessible for neutralizing antibody binding. Immunization with the vaccine elicited high and long-lasting neutralizing antibodies and effectively protected mice against the challenges of lethal H1N1 or heterosubtypic H5N8, as well as the SARS-CoV-2 Delta or Omicron BA.2 variants. Overall, this study offers a two-in-one universal vaccine design to combat infections caused by both SARS-CoV-2 variants of concern and influenza viruses.